Comparative analysis of service quality of health care systems: case of the emergency department of a government hospital in Southwestern Nigeria (2024)
The health industry's role is vital in the preservation and elongation of the lives of many people. The emergency department in any hospital is designed to handle delicate health situations. An emergency department without adequate capacity to handle these situations would frequently record mortality. Service quality in any establishment is an important performance indicator. Therefore, this study aimed to evaluate the service quality in the emergency department of a chosen hospital. Using SERVAQUAL and Taguchi (mini-tab software and excel package) approaches, factors affecting the quality of service in the department were identified; perception data on the quality of service available to patients were collected through questionnaires under five sections; analyzed and compared. While identified factors include the number of health workers – doctors and nurses, number of bed spaces and retention period of patients, the five sections in the questionnaires covered Tangibles, Reliability, Assurance, Responsiveness and Empathy. Responses recorded totaled one hundred and two (102). Taguchi analysis (mini-tab software) revealed that the presence of nurses played the most vital role in the survival of patients brought into the department, as it ranked first (1st) among the other factors. Excel software showed Empathy as the factor with the highest perception data score of 364.4, while Tangibles had the lowest perception score of 340. From the SERVAQUAL analysis, the patient's perception of Empathy revealed the importance of emergency nursing care, aligning with results from the Taguchi analysis. The need for better infrastructure and equipment within the department was also identified as an area that would increase the quality of service since these had the lowest perception in the patients' minds (Tangibles). Evaluation of the quality of service provided in an emergency department of a government hospital using Taguchi and SERVAQUAL approaches gave similar results, with Empathy and Tangibles playing critical roles in patients' survival.